2003
DOI: 10.1080/09500690210145819
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theory of curriculum implementation with particular reference to science education in developing countries

Abstract: Improving science education is often regarded as a priority for developing countries in order to promote longterm economic development. Thus initiatives, both government and foreign-aid sponsored, aimed at improving science education in developing countries abound. However, all too often the focus of such initiatives is limited to the development of science curricula, while the details of how the curricula will be implemented at school level are often neglected. This paper represents an effort to lay the groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
222
2
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(235 citation statements)
references
References 16 publications
3
222
2
8
Order By: Relevance
“…The researcher reasons that the end product from the universities would be a raw one considering the fact that most lecturers concentrated only on theory leaving out the practical aspect of the subject as earlier stated and now it has been exposed that the same lectures did not teach the entire topics they are supposed to teach. Furthermore, Verspoor (1989: 133) in Rogan and Grayson (2003) Porter (2006) also argues that the curricula are well designed with aims that are praiseworthy but all too often the attention and energies of policymakers are focused on the 'what' of desired educational change, neglecting the 'how' and this hampers the delivery of the programme.…”
Section: No Products From Universities Are Not Competent Since They mentioning
confidence: 99%
See 2 more Smart Citations
“…The researcher reasons that the end product from the universities would be a raw one considering the fact that most lecturers concentrated only on theory leaving out the practical aspect of the subject as earlier stated and now it has been exposed that the same lectures did not teach the entire topics they are supposed to teach. Furthermore, Verspoor (1989: 133) in Rogan and Grayson (2003) Porter (2006) also argues that the curricula are well designed with aims that are praiseworthy but all too often the attention and energies of policymakers are focused on the 'what' of desired educational change, neglecting the 'how' and this hampers the delivery of the programme.…”
Section: No Products From Universities Are Not Competent Since They mentioning
confidence: 99%
“…Some students thought CT was about fabrics and sewing only, but after enrolling to study CT at university level, they were made to realise that there was more to it than just fabrics. According to Rogan and Grayson (2003) students are not motivated to learn if they don't realise the importance of a learning programme. However, on the contrary, some students regretted why they chose CT for it was seen as a programme for low academic achievers.…”
Section: When L Joined the University L Had A Negative Perception Abomentioning
confidence: 99%
See 1 more Smart Citation
“…This perspective is referred to here as the zone of proximal implementation. Vygotsky's concept of the zone of proximal development Á the distance between what learners can accomplish independently and what they can accomplish through guidance or collaboration Á has previously been applied to largescale reform (Rogan 2007;Rogan and Grayson 2003); school leadership (McGivney and Moynihan 1972); and the mediation of educational partnerships (Oakes et al 1998). Similarly, others have referred to the need to pursue certain innovation goals in stepwise fashion, gradually moving from the current situation toward what is desired (e.g.…”
Section: Toward Relevant Tel Research Within the Zone Of Proximal Impmentioning
confidence: 99%
“… Inadequate financial support (Rogan & Grayson, 2003), which results in poor educational resources and very limited quality training opportunities for HoDs and teachers,  Poor coordination of student internship and inadequate provision of practical training in the vocational institution, which result in students having theoretical knowledge about the discipline but little mastery of the target vocational skills (Akomaning et al, 2011;Lumby, 2000) as reported in this study,  High rate of HoDs' and teachers' mobility and attrition in developing contexts due to their search for better job offers (Gervedink Nijhuis et al, 2012), thereby increasing the number of adjunct teachers who are usually less qualified and are not required to participate in CD activities (Diamond, 2008),  Lack of CD expertise and management skills of the academic managers as most of them are promoted to such leading positions based on teaching seniority and oftentimes without attending pre-or in-service relevant training programs (Gervedink Nijhuis et al, 2012). This probably makes them play a reactive rather than a proactive role regarding curriculum development issues, which is not appreciated by the HoDs and teachers as found in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 99%